Analysis of Blended Learning on Student Interest in Physical Education for 10th Grade High School - Anwar, Khiorul; Firmansyah, Ihwan; Andriani, Miranti Widi (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
Blended learning is an important learning model application for today's needs, with meetings through e-learning and face-to-face. Basically, the purpose of this research is to observe carefully and then carry out a thorough discussion of the application of learning activities using the blended learning method, which is linked and linked to interest in learning PJOK. This type of research is descriptive quantitative with a survey method. The sample used is the students of SMAN 2 Bangkalan class X, with as many as 103 respondents. The data collection method used a questionnaire distributed online at the school. The data were then analyzed using percentage calculations. Based on the research results, most of them are categorized as very low 9%, low 19%, moderate 45%, high 22%, and very high 5%. The results of this research can be interpreted that the implementation of learning using a blended learning approach to interest in learning PJOK subjects is moderate. The conclusion is that the implementation of blended learning is in the medium category, which means that it is not very interesting for students in PJOK subjects. Improving facilities as learning support using a blended learning approach to increase interest in PJOK subjects is a suggestion that can be given from research results.